Identification of small-molecule inhibitors of Yersinia pestis Type III secretion system YscN ATPase. - Wieslaw Swietnicki (Public Library of Science (PLoS), 2011)
Yersinia pestis is a gram negative zoonotic pathogen responsible for causing bubonic and pneumonic plague in humans. The pathogen uses a type III secretion system (T3SS) to deliver virulence factors directly from bacterium into host mammalian cells. The system contains a single ATPase, YscN, necessary for delivery of virulence factors. In this work, we show that deletion of the catalytic domain of the yscN gene in Y. pestis CO92 attenuated the strain over three million-fold in the Swiss-Webster mouse model of bubonic plague. The result validates the YscN protein as a therapeutic target for plague. The catalytic domain of the YscN protein was made using recombinant methods and its ATPase activity was characterized in vitro. To identify candidate therapeutics, we tested computationally selected small molecules for inhibition of YscN ATPase activity. The best inhibitors had measured IC(50) values below 20 µM in an in vitro ATPase assay and were also found to inhibit the homologous BsaS protein from Burkholderia mallei animal-like T3SS at similar concentrations. Moreover, the compounds fully inhibited YopE secretion by attenuated Y. pestis in a bacterial cell culture and mammalian cells at µM concentrations. The data demonstrate the feasibility of targeting and inhibiting a critical protein transport ATPase of a bacterial virulence system. It is likely the same strategy could be applied to many other common human pathogens using type III secretion system, including enteropathogenic E. coli, Shigella flexneri, Salmonella typhimurium, and Burkholderia mallei/pseudomallei species.